The factors of technology acceptance influencing mobile apps in tourism among local tourists in Malaysia - Ahmad Iskandar Adrian Muzaffar; Chiang Zhi Ying; Nor Erynazatul Ain Hamdan; Nurul Ashyiqin Asrin (2021)
The purpose of this research is to identify the relationship between social media, travel applications and flexibility towards technology acceptance in tourism among local tourist in Malaysia. The main objective for this research is to investigate the factors of technology acceptance influencing mobile apps in tourism and a better knowledge and understanding that affect local tourist in Malaysia. A total of 292 respondents were participated in online survey whom mainly the local tourists in Malaysia. Pearson correlation coefficient used to determine on the link of independent variables towards factors associated with local tourist in Malaysia. The results indicate significant relationship between social media, travel applications, and flexibility with the technology acceptance. This study shows that social media and travel application give a big influence in technology acceptance in tourism among local tourist in Malaysia.